Efficiency of three dimension Au–MnO2 nanostructure as visible adsorption based detector of histamine sensing - Siti Febtria Asrini Sugito; Mochamad Zakki Fahmi; Miratul Khasanah; Septianti Putri Sophiar; Jia-yaw Chang; Gasidit Panomsuwan (Sensors International)
High intakes of histamine are poisonous. Hence, determining histamine levels in fisheries and processed products is essential to food quality. Several colorimetric sensors based on gold nanoparticles have shown exemplary performance in detecting the presence of histamine in samples. The modified AuNPs by MnO2 were used as a reagent in histamine analysis by UV–Vis spectrophotometry. Using a seed-mediated growth method, modified Au–MnO2 nanostructures were synthesized from citrate-coated AuNPs and KMnO4. The Au–MnO2 nanostructure synthesis process produced a yellow-green solution, which produced a crystalline solid with a particle size <100 nm by evaporation. These nanoparticles comprise AuNPs and MnO2 components, which still perform their original properties. Application of Au–MnO2 nanostructure in histamine spectrophotometry has values in sensitivity of 0.0344 ppm, detection limit of 0.185 ppm, quantification limit of 0.618 ppm, and accuracy of 95–101 %. Based on analytical results, the effectiveness of synthesizing Au–MnO2 nanostructure to form complexes with histamine content was low, and it was due to the weak binding between the imidazole group of histamine and Au–MnO2 nanostructures. Therefore, further investigation on the composition of the Mn metal or the selection of other metals is needed to use Au–MnO2 as candidate histamine biosensors.